The Effect of Using Ausubel's Assimilation Theory and the Metacognitive Strategy (K.W.L) in Teaching Probabilities and Statistics Unit for First Grade Middle School Students’ Achievement and Mathematical Communication - Abdul-Rehman Al Tamimi (European Scientific Journal, ESJ, 2017)
The study aimed to investigate the effect of using Ausubel's assimilation theory and the metacognitive strategy (K.W.L) in teaching statistics and probability unit for students of second grade – middle school students’ achievement and mathematical communication. The study sample consisted of 168 grade – middle school students in Hail. They were randomly divided into two experimental groups; the first (N=56) students and the second (N=56), and a control group (N=56). The first experimental group was studied using Ausubel's model; the second experimental group was studied using the metacognitive strategy (K.W.L); and the control group was studied using the conventional method. The research tools used in this study is an achievement test and scale for mathematical communication. The results showed that there were significant differences in achievement for the first and the second experimental group compared to the control group. Hence, this demonstrates the effectiveness of these two methods in teaching. The results showed statistically significant differences in mathematical communication due to the teaching methods. In addition, the second experimental group outperformed the first experimental group and the control group. The results also showed a statistically significant difference between pre-administration and the postadministration in favor of the post-administration for the three research groups. Further recommendations were suggested for future research.